Living With Intelligent Sensors: Older Adult and Family Member Perceptions. Issue 12 (December 2019) - Galambos, Colleen; Rantz, Marilyn; Craver, Andy; Bongiorno, Marie; Pelts, Michael; Holik, Austin John; Jun, Jung Sim
Abstract : This qualitative study is part of a larger randomized prospective intervention study that examined the clinical and cost effectiveness of using sensor data from an environmentally embedded sensor system for early illness recognition. It explored the perceptions of older adults and family members on the sensor system's usefulness, impact on daily routine, privacy, and sharing of health information. This study was conducted in 13 assisted-living facilities in Missouri, and 55 older adults were interviewed. Data were collected over five points in time with a total of 188 interviews. From these five participant interview iterations, the following themes emerged: (1) understanding and purpose, (2) daily life and benefits, (3) impact on privacy, and (4) sharing of information. Three themes emerged from one round of family interviews: (1) benefits of bed sensors, (2) family involvement/staff interaction, and (3) privacy protection versus sensor benefits. The sensor suite was regarded as helpful in maintaining independence, health, and physical functioning. Responses suggest that the willingness to adopt the sensor suite was motivated by both a decline in functional status and a desire to remain independent. Participants were willing to share their health data with providers and select family members. Recommendations for future practice are provided.